Video guide to DNA biotechnology - Science Vision International (Shrewsburry : Science Vision International)
This video has been designed to provide the basic principles and applications of the common molecur biology techniques used in research and industry. vol.1 - Introduction, structure of chromosomes, DNA structure and replication - vol.2 - Introduction to plasmids, plasmid preparation, restriction & modifying enzymes
Keywords: Biotechnology -- study and teaching; DNA